Dynamic testing and analysis of the world's first metal 3D printed bridge. (December 2022) - Wynne, Zachariah; Buchanan, Craig; Kyvelou, Pinelopi; Gardner, Leroy; Kromanis, Rolands; Stratford, Tim; Reynolds, Thomas P.S.
Abstract: The MX3D Bridge is the world's first additively manufactured metal bridge. It is a 10.5 m-span footbridge, and its dynamic response is a key serviceability consideration. The bridge has a flowing, sculptural form and its response to footfall was initially studied using a 3D finite element (FE) model featuring the designed geometry and material properties obtained from coupon tests. The bridge was tested using experimental modal analysis (EMA) and operational modal analysis (OMA) during commissioning prior to installation. The results have shown that the measured vibration response of the bridge under footfall excitation is 200% greater than predictions based on the FE model and contemporary design guidance. The difference between predicted and measured behaviour is attributed to the complexity of the structure, underestimation of the modal mass in the FE model, and the time-variant modal behaviour of the structure under pedestrian footfall. Both OMA and EMA give a dominant natural frequency for the bridge of between 5.19 Hz and 5.32 Hz, higher than the FE model prediction of 4.31 Hz, and average damping estimates across all modes of vibration below 15 Hz of 0.61% and 0.74% respectively, higher than the 0.5% assumed within the design guidance, slightly reducing the peak response factor predicted for the bridge. Graphical Abstract: ga1 Highlights: Quantifies the dynamic response of a metal 3D printed bridge. Compares the measured vibration response with that predicted using design guidance. Compares finite element model, experimental and operational modal analysis results. Identifies the sensitivity of results to modal mass estimates. Highlights benefits of ambient vibration testing for accurate parameter estimates.